Queen's Park Hotel, Trinidad - (:unkn) unknown (My University, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. In the postcard, taxis can be seen parked outside the Hotel.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; [1930]; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)